Racing with Collaboration: Enhancing Innovation through Leveraging Social Networks and Knowledge Management in Competitive Business - Susantinah Wisnujati, Nugrahini (PT. LITERASI SAINS NUSANTARA, 2024)
In the era of globalization and increasingly fierce business competition, innovation has become the primary key to a company's success. Companies that continuously generate new innovations possess a significant competitive advantage, enabling them to sustain and thrive in rapidly changing markets. However, the primary challenge for companies today is how to optimize their innovation processes in continually evolving and complex contexts. This research aims to explore the role of social networks and knowledge management in enhancing innovation in competitive business environments, with a focus on the potential for inter-company collaboration. This research method employs a qualitative approach, focusing on literature review and descriptive analysis. Initially, literature search was conducted through Google Scholar with a time frame from 2000 to 2024. The study findings indicate that in the era of globalization and increasingly fierce business competition, the traditional paradigm emphasizing pure competition has shifted. Collaboration and innovation have become the foundation for success and sustainable competitive advantage. Leveraging social networks, knowledge management, and a collaborative-supportive work culture are key to creating an environment that fosters sustainable growth and innovation. The utilization of technology also plays a crucial role in strengthening social networks and facilitating effective knowledge management.